STRATEGI SUTRADARA DALAM PENGELOLAAN PRODUKSI WEB SERIES COMPANY PROFILE SEBAGAI MEDIA KOMUNIKASI BRAND HALAMAN OMAH - Maharani, Regita Aura; Priatna, Wahyu Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growing dominance of short-form video content on social media has encouraged brand communication practitioners to develop more strategic approaches to audiovisual production. This study investigates the director’s role and strategies in producing a company profile web series for Halaman Omah Coffee Shop, Bogor, which was distributed through Instagram Reels as a brand communication channel. A qualitative descriptive approach with project-based documentation was employed, with the researcher acting simultaneously as the director and researcher throughout the pre-production, production, and post-production processes. Data collection was conducted through direct observation, production records, stakeholder feedback, and limited audience testing. To ensure the trustworthiness of the findings, source triangulation and member checking techniques were applied.The results indicate that the director’s strategic involvement played a crucial role in aligning brand communication goals with narrative development and audiovisual execution. During the pre-production phase, a storytelling concept was developed through a brand discovery process and translated into four interconnected episodes, each carrying a distinct thematic focus. In the production stage, decisions related to framing, talent direction, cinematographic treatment, and crew management were consistently guided by the intention to portray Halaman Omah as a warm, welcoming, and family-oriented café. Meanwhile, post-production activities, including footage selection, editing structure, color grading, and sound design, were carefully managed to maintain visual consistency and strengthen the overall brand identity.Furthermore, the findings suggest that the web series format provides an effective mechanism for gradually building audience engagement through continuous storytelling across episodes. This study contributes academically by offering a director-oriented perspective on audiovisual brand communication within Indonesia’s short-form video environment. From a practical standpoint, it presents a production model that can be adapted by small and medium-sized enterprises seeking to utilize Instagram Reels as a strategic platform for brand development and audience engagement.